Exposition of Internal Factors Enhancing Creativity and Knowledge Creation - Girdauskiene, Lina; Savaneviciene, Asta (Knowledge Discovery, Knowledge Engineering and Knowledge Management, 2015)
A creative organization is distinguished among traditional organizations. Creative organizations are trying to strike a balance between business and creativity when creating a proper environment for knowledge management, at the same time, encourages employees to develop creative work and produce new products that meet market needs. Thus, the research purpose is defined as follows: what features of internal factors do influence creativity and knowledge creation in a creative organization? A qualitative research method, based on a scientific analysis and identification of the key factors, allowed reveal the features of a task, group and time influencing creativity and knowledge creation in a creative organization. The research results show that different features of tasks, group and time make an impact on different employee groups, types of creativity and knowledge in a creative organization.